Hypothiocyanous Acid Disrupts the Barrier Function of Brain Endothelial Cells - Eveline van Leeuwen; Mark B. Hampton; Leon C. D. Smyth (MDPI AG, 2022)
Inflammation is a common feature of neurological diseases. During neuroinflammation, neutrophils are recruited to the brain vasculature, where myeloperoxidase can produce hypochlorous acid and the less well-studied oxidant hypothiocyanous acid (HOSCN). In this study, we exposed primary brain endothelial cells (BECs) to HOSCN and observed a rapid loss of transendothelial electrical resistance (TEER) at sublethal concentrations. Decreased barrier function was associated with a loss of tight junctions at cellular contacts and a concomitant loss of dynamic microtubules. Both tight junction and cytoskeletal disruptions were visible within 30 min of exposure, whereas significant loss of TEER took more than 1 h. The removal of the HOSCN after 30 min prevented subsequent barrier dysfunction. These results indicate that BECs are sensitive to HOSCN, resulting in the eventual loss of barrier function. We hypothesise that this mechanism may be relevant in neutrophil transmigration, with HOSCN facilitating blood-brain barrier opening at the sites of egress. Furthermore, this mechanism may be a way through which neutrophils, residing in the vasculature, can influence neuroinflammation in diseases.